Empowered milk: How 'swakrushi' milk is empowering India's women livestock keepers - International Livestock Research Institute (International Livestock Research Institute, 2020)
Started by women in 2002, the Mulukanoor Women’s Cooperative Dairy in Telangana, India has evolved into one of India’s more successful dairy businesses, producing milk and milk products on a 24/7 basis. How did they achieve this? This film tells a story of improved fodder, more productive dairy cows, high-quality milk, and economically empowered women smallholder livestock keepers. Read more in the ILRI 2019 Annual Report: https://www.ilri.org/news/annual-repo...